Herd composition and slaughtering strategy in reindeer husbandry – revisited - Holand, Øystein (Rangifer, 2007)
I will review the drastic change seen in herd composition and slaughtering strategy the last decades inthe reindeer husbandry of Fennoscandia (i. e. Finland, Norway and Sweden). Herd composition was traditionally a function of the multipurpose herd, where reproduction of draught power played a major role. Hence, the slaughter scheme was based on adult males, in particular castrates. The herd represented the owner's capital and was viewed as the best insurance for staying in business. Indeed, a big and well composed herd announced social status as well as authority. Historically this has resulted in rises and falls in reindeer numbers. Control of the herd was being emphasized through age and sex composition and selection of behavioural traits and easily recognisable animals which favour handling. A high proportion of adults alleviated control of the herd as it eased the herding and reduced the mortality risk as they were able to withstand the highly stochastic environment. The introduction of the snowmobiles in the 1960s revolutionized the herding and transportation and hence reduced the importance of the male segment of the herd and amplified the ongoing transformation of the modern society into a market based economy. Now, the challenge was to efficiently convert the limited primary plant production into animal product, mainly meat. This is primarily achieved by balancing the animal numbers in accordance to the forage resources. However, also herd composition and slaughtering strategy are essential for maximizing the meat output per area unit. A highest possible proportion of reproductive females combined with a slaughtering scheme based on calves was tested and partly implemented in Soviet-Union already in the 1930s and introduced in the 1960s in Finland. Also in parts of Norway and Sweden this scheme was modified and tested. However, the formal work of refining and testing this new strategy based on modern population theory blended with traditional knowledge, started in Riast/Hylling reindeer herding district ...